Therapeutic Effects of Patchouli (Pogostemon cablin) Essential Oil in Relieving Eczema Symptoms in Infants and Toddlers: A Literature Review - Deliana, Fitri; Illian, Didi Nurhadi; Nadirah, Siti; Sari, Fadia; Khairan, Khairan (Universitas Syiah Kuala, 2023)
This literature review aims to investigate and analyze the therapeutic effect of Patchouli essential oil (Pogostemon cablin) in alleviating eczema symptoms in infants and young children. Eczema is a common skin condition characterized by inflammation, itching, and redness that can significantly affect the quality of life of affected children and their families. Conventional treatments often use topical corticosteroids, which can have potential side effects. This review systematically examines relevant studies, articles, and research from reputable databases, focusing on the use of patchouli essential oil as an alternative therapeutic approach to treat eczema symptoms in the pediatric population. Several aspects are considered, including the chemical composition of patchouli essential oil, its potential mechanisms of action, and its reported efficacy in reducing inflammation and relieving itching associated with eczema. The results of the literature review suggest that patchouli essential oil possesses anti-inflammatory, antimicrobial, and antioxidant properties that may contribute to its therapeutic effect in the treatment of eczema. Several studies have reported positive results, including a reduction in erythema, itching, and overall severity of eczema symptoms in infants and young children. However, the literature also has some limitations, such as the lack of standardized protocols, varying study designs, and limited long-term follow-up data. Overall, this literature review provides valuable insights into the therapeutic effects of patchouli essential oil in alleviating eczema symptoms in infants and young children. Further well-designed studies are needed to determine the optimal dosage, formulation, and long-term safety profile. The results of this review contribute to the growing body of knowledge on alternative treatments for pediatric eczema and provide a foundation for future research and clinical applications in this area.